IMPLEMENTASI DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN MOBIL DI SHOWROOM JATI SUBUR LEWAT APLIKASI FACEBOOK - Indra, Ramadhan; Fitriyah, Zumrotul (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The digital transformation era has driven business actors, including used car dealers, to adopt social media-based marketing technologies. Jati Subur Mobil (JSM), a used car showroom located in Rungkut Alang-Alang No. 195, Surabaya, has utilized Facebook as a marketing platform to increase its vehicle sales. This study aims to analyze the impact of Facebook application usage in the digital marketing strategy at JSM. The research uses a descriptive qualitative method with a case study approach. Results indicate that Facebook effectively increases customer reach and enhances car sales by 20%. Key strategies include the use of Facebook Marketplace, buy-and-sell groups, and the creation of aesthetic and cinematic content to attract customers emotionally and visually. This case highlights the importance of consistent content publishing, responsive interaction with potential buyers, and optimal use of Facebook features to build engagement and drive sales. The findings can serve as a practical guide for new entrepreneurs in the automotive retail industry seeking to leverage digital platforms like Facebook for business growth.